Kan man ingjuta mer liv i Norra Fäladens centrum? - Werner, Elin (2009)
This is a master thesis on how to develop the central area of Norra Fäladen, a suburban housing area in the town of Lund, Sweden. The area is discussed on the basis of literature studies, analysis, and place descriptions, which leads on to a proposal. The starting point for the proposal is to create a more lively local centre and to make the area pleasanter for the visitor. A large part of the thesis is devoted to giving a background about local centres and to describe and analyse the area.